2019
DOI: 10.1186/s12891-018-2396-9
|View full text |Cite
|
Sign up to set email alerts
|

The first 100 patients treated with a new anatomical pre-contoured locking plate for clavicular midshaft fractures

Abstract: BackgroundPre-contoured locking plates were recently introduced in the management of clavicular midshaft fractures. These plates may offer advantages such as no necessity for intraoperative bending and reduced plate irritation. The purpose of this study was to review the clinical and radiographical outcome of the first 100 patients treated with a new anatomical pre-contoured locking plate.MethodsIn a retrospective single-center study, 100 consecutive patients (16 female, 84 male) with a median age of 40 years … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 24 publications
0
13
1
Order By: Relevance
“…All the disadvantages described above might increase operation time in the traditional group. Importantly, the mean operation time of the Nice knot group in the current study (78.56 min) was even less than some previous reports(70-100 min) of open plating for midshaft clavicle fractures [21,22,23]. Additionally, the proportion of Type 2B2 fractures was signi cantly higher in the Nice knot group, which seemed to hint that the method is more suitable for this type of complicated fractures.…”
Section: Discussioncontrasting
confidence: 63%
“…All the disadvantages described above might increase operation time in the traditional group. Importantly, the mean operation time of the Nice knot group in the current study (78.56 min) was even less than some previous reports(70-100 min) of open plating for midshaft clavicle fractures [21,22,23]. Additionally, the proportion of Type 2B2 fractures was signi cantly higher in the Nice knot group, which seemed to hint that the method is more suitable for this type of complicated fractures.…”
Section: Discussioncontrasting
confidence: 63%
“…Importantly, the mean operation time of the Nice knot group in the current study (78.56 min) was even less than some previous reports (70–100 min) of open plating for midshaft clavicle fractures. [ 20 22 ] Additionally, the proportion of Type 2B2 fractures was significantly higher in the Nice knot group, which seemed to hint that the method is more suitable for this type of complicated fractures.…”
Section: Discussionmentioning
confidence: 94%
“…Hardware prominence was less when precontoured plate was used. Tania Reisch et al [17] in their research in 100 patients found the new precontoured locking plate fit to the anatomical shape of the clavicle. The implant seems to be reliable regarding handling and complications.…”
Section: Discussionmentioning
confidence: 98%